PEMASANGAN LAMPU TENAGA SURYA SEBAGAI PENERANGAN RAMAH LINGKUNGAN DIKAMPUNG MANDIRI JAYA - Longginus Gelatan; Marvelia C Haurissa; Patricia J Sharon; Febyola D Dawes; Anjelita R Wenehen (JOURNAL OF COMMUNITY DEDICATION, 2026)
This community service activity aims to address the lack of street lighting inMandiri Jaya Village.  Using a participatory approach, the implementation team and local residents conducted a needs assessment, preparation, installation, and evaluation of solarpowered street lights.The results of the community service activity showed that all installed solar street lights function properly and significantly improve the quality of road illumination. The results of this activity had a positive impact such as increased sense of security, improved comfort for night time activities, and community mobility.Overall, the program proves effective in supporting the improvement of village infrastructure quality and promoting sustainable development based on environmentally friendly energy solutions.